2013
DOI: 10.1016/j.kjms.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence and second primary tumors in oral squamous cell carcinoma treated with surgery alone

Abstract: The aim of the present study is to review the recurrence patterns and incidence of second primary tumors (SPTs) in patients with oral squamous cell carcinoma (OSCC) who underwent surgery alone without postoperative adjuvant therapy. Data on patients recorded in the head and neck cancer registry of Cathay General Hospital were reviewed. A total of 72 patients with T1-3N0 OSCC who underwent surgery alone were included. Among the 72 patients, 44 had T1 tumors, 22 had T2 tumors, and 6 had T3 tumors. The 5-year ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 19 publications
5
39
1
1
Order By: Relevance
“…The rising incidence and survival rates lead to an increasing OCC prevalence, which poses challenges for surveillance care. Patients treated with curative intent receive an intensive follow‐up regimen, comprising at least 17 check‐up visits within 5 years to detect recurrence and second primary head and neck cancers early . Furthermore, because of the negative impact of treatment on oral function, patients will not only rely on their medical specialist, but also on an array of supportive specialties, such as dentists, dieticians and physical therapists.…”
Section: Discussionmentioning
confidence: 99%
“…The rising incidence and survival rates lead to an increasing OCC prevalence, which poses challenges for surveillance care. Patients treated with curative intent receive an intensive follow‐up regimen, comprising at least 17 check‐up visits within 5 years to detect recurrence and second primary head and neck cancers early . Furthermore, because of the negative impact of treatment on oral function, patients will not only rely on their medical specialist, but also on an array of supportive specialties, such as dentists, dieticians and physical therapists.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, surgical treatment is preferred in the initial oral cancer, and the cases of progressed oral cancer with cervical lymph node metastasis can be provided with surgical treatment along with chemotherapy and radiation therapy [22]. Previous studies reported that overall survival and disease-specific survival was significantly higher in the surgically treated group compared with no surgery group in oral cavity squamous cell carcinoma [2325]. Surgery and/or radiation therapy provides disease-specific survival benefit as compared with no therapy within the head and neck region [26].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies on follow‐up after treatment for OSCC are scarce and usually combine the data of all HNC's, which have a different etiology, treatment, prognosis, and timing of second events . The available studies on OSCC are small and do not address the question whether specific patient groups are in need of more or less intensive follow‐up …”
Section: Introductionmentioning
confidence: 99%